2012
DOI: 10.1136/archdischild-2011-300888
|View full text |Cite
|
Sign up to set email alerts
|

Early term and late preterm birth are associated with poorer school performance at age 5 years: a cohort study

Abstract: Late preterm and early term birth are associated with an increased risk of poorer educational achievement at age 5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
177
6
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(208 citation statements)
references
References 38 publications
15
177
6
10
Order By: Relevance
“…Although childbirth at 38 weeks of gestation may be associated with a potential reduction in LGA infants, some evidence suggests that early term birth (o39 weeks) is associated with increased risk of neonatal illness and mortality (Sengupta et al, 2013;Mally et al, 2015), as well as long-term morbidity including lower educational attainment (Marlow, 2012;Quigley et al, 2012). In our study, GDM mothers were induced earlier compared to the NGT mothers, and they also had elective caesarean sections earlier than their NGT counterparts.…”
Section: Discussionmentioning
confidence: 52%
“…Although childbirth at 38 weeks of gestation may be associated with a potential reduction in LGA infants, some evidence suggests that early term birth (o39 weeks) is associated with increased risk of neonatal illness and mortality (Sengupta et al, 2013;Mally et al, 2015), as well as long-term morbidity including lower educational attainment (Marlow, 2012;Quigley et al, 2012). In our study, GDM mothers were induced earlier compared to the NGT mothers, and they also had elective caesarean sections earlier than their NGT counterparts.…”
Section: Discussionmentioning
confidence: 52%
“…35 They have also been found not to reach a good level of overall achievement in early school by teacher assessments using the Foundation Stage Profile. 36 In contrast to reports of increased difficulties, 1 group out of Northern Ireland found equal testing scores for cognitive, language, and motor abilities between LPIs that required intensive care and those that did not, without FTI controls, in a homogeneous population. 37 Gurka et al reported no differences between LPIs and FTIs in cognitive, achievement, behavioral/emotional, or social disability at 15 years of age.…”
Section: Figurementioning
confidence: 65%
“…9 Infants born at 37 to 38 weeks' gestation have been shown to have an increased risk for readmission for jaundice previously 10 ; however, the impact of early discharge on these infants has not been investigated. An increasing amount of research about early term infants has shown these infants have more neonatal morbidity, 20 poorer long-term general health, 21 higher health service use and costs, 13 and poorer educational results 22 than infants born at 39 to 41 weeks' gestation.…”
Section: Figurementioning
confidence: 99%